Goethe's Cyclical Narratives "Die Unterhaltungen deutscher Ausgewanderten" and "Wilhelm Meisters Wanderjahre" - Brown, Jane K. (UNC Studies in the Germanic Languages and Literatures, 1975)
The novelty of this study lies in its techniques for understanding the deliberate narrative contradictions and elusive parody in Goethe's work. Interpretation of the entire "Unterhaltungen", including the Märchen, establishes Goethe's principles of cyclical composition. By pursuing the elaboration of these principles in the "Wanderjahre"-the undependable narrator, multiple perspectives, and parody of popular eighteenth-century figures-the author interprets the cultural and social significance of Goethe's most sophisticated novel.